2019
DOI: 10.3389/fimmu.2019.02702
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Inflammation Induces Differential Cytokine Patterns and Apoptosis in Dendritic Cells

Abstract: The activation of dendritic cells (DCs) has profound implications and governs the control of adaptive immunity. However, long-term activation might drive exhaustion of immune cells and negatively affect functionality. Here, long-term vs. short-term exposure to bacterial lipopolysaccharide and interferon (IFN)γ was evaluated on human monocyte-derived DCs. Long-term activated DC1s began to undergo apoptosis concomitant with a profound TAM-receptor and efferocytosis-dependent induction of interleukin (IL)-10. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…However, there is a strong correlation between this subset of DCs and the exhausted CD8 + T cell and Treg cell signature within the TME, implying that this subset of intratumoral DCs might be related to T cell dysfunction, despite their maturation features ( Zhang et al, 2019 ). Moreover, the ability to expand antigen-specific CD8 + T cells is a feature of specialized effector DCs at early stages of maturation, and it is suppressed in exhausted DCs at late stages of maturation and in DCs matured under the conditions of chronic inflammation ( Abdi et al, 2012 ; Carstensen et al, 2019 ; Rodrigue-Gervais et al, 2010 ). Long-term activation of DCs under conditions of chronic inflammation and cancer impairs their functionality, and a lack of IL-12 secretion results in non-functional T cells devoid of IFN-γ ( Carstensen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a strong correlation between this subset of DCs and the exhausted CD8 + T cell and Treg cell signature within the TME, implying that this subset of intratumoral DCs might be related to T cell dysfunction, despite their maturation features ( Zhang et al, 2019 ). Moreover, the ability to expand antigen-specific CD8 + T cells is a feature of specialized effector DCs at early stages of maturation, and it is suppressed in exhausted DCs at late stages of maturation and in DCs matured under the conditions of chronic inflammation ( Abdi et al, 2012 ; Carstensen et al, 2019 ; Rodrigue-Gervais et al, 2010 ). Long-term activation of DCs under conditions of chronic inflammation and cancer impairs their functionality, and a lack of IL-12 secretion results in non-functional T cells devoid of IFN-γ ( Carstensen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ability to expand antigen-specific CD8 + T cells is a feature of specialized effector DCs at early stages of maturation, and it is suppressed in exhausted DCs at late stages of maturation and in DCs matured under the conditions of chronic inflammation ( Abdi et al, 2012 ; Carstensen et al, 2019 ; Rodrigue-Gervais et al, 2010 ). Long-term activation of DCs under conditions of chronic inflammation and cancer impairs their functionality, and a lack of IL-12 secretion results in non-functional T cells devoid of IFN-γ ( Carstensen et al, 2019 ). Fascin inhibition, IL-4 inhibition, and CD40 activation, together with anti-PD-1 antibody, could release the inhibition and re-activate these DCs ( Garris et al, 2018 ; Maier et al, 2020 ; this study).…”
Section: Discussionmentioning
confidence: 99%
“…Direct effects include damage to functional macromolecules and increased activation of apoptotic pathways (199,200). Indirect effects include increased Wnt signalling (90), epigenetic dysregulation and compromised TLR activity (201)(202)(203).…”
Section: Redox Regulation Of DC Activation and Functionmentioning
confidence: 99%
“…103,104 IFN also functions in tumors, showing an anti-tumor role of IFN-g. Long-term-activated DCs fail to effectively activate alloreactive IFN-g-responsive T cells, and they changed their profile toward a non-functional and tumor-promoting phenotype. 105 In addition, in the last step of efferocytosis, Cunha et al 106 showed that tumor-associated macrophages with LC3-associated phagocytosis (LAP) displayed M2 characteristics and reduced secretion of IFN-g, which suppressed the anti-tumor response. TAM lacking LAP exhibited M1 characteristics and increased stimulator of IFN genes (STING)dependent type I IFN production to promote IFN-g, resulting in anti-tumor responses.…”
Section: Ifnmentioning
confidence: 99%